Arthropod-Microbiota Integration: Its Importance for Ecosystem Conservation - Schapheer, Constanza; Pellens, Roseli; Scherson, Rosa (Frontiers in Microbiology, 2021)
Recent reports indicate that the health of our planet is getting worse and that genuine transformative changes are pressing. So far, efforts to ameliorate Earth’s ecosystem crises have been insufficient, as these often depart from current knowledge of the underlying ecological processes. Nowadays, biodiversity loss and the alterations in biogeochemical cycles are reaching thresholds that put the survival of our species at risk. Biological interactions are fundamental for achieving biological conservation and restoration of ecological processes, especially those that contribute to nutrient cycles. Microorganism are recognized as key players in ecological interactions and nutrient cycling, both free-living and in symbiotic associations with multicellular organisms. This latter assemblage work as a functional ecological unit called “holobiont.” Here, we review the emergent ecosystem properties derived from holobionts, with special emphasis on detritivorous terrestrial arthropods and their symbiotic microorganisms. We revisit their relevance in the cycling of recalcitrant organic compounds (e.g., lignin and cellulose). Finally, based on the interconnection between biodiversity and nutrient cycling, we propose that a multicellular organism and its associates constitute an Ecosystem Holobiont (EH). This EH is the functional unit characterized by carrying out key ecosystem processes. We emphasize that in order to meet the challenge to restore the health of our planet it is critical to reduce anthropic pressures that may threaten not only individual entities (known as “bionts”) but also the stability of the associations that give rise to EH and their ecological functions.